Pengukuran waktu baku dan analisis beban kerja untuk menentukan jumlah optimal tenaga kerja pada proses cetak produk lipstick - Aisyah Syifa Ramadhani (Universitas Mercu Buana, 2020)
PT Astoria Prima is a manufacturing company that runs in the field of cosmetic products, currently the company does not yet have a perfect time standard to be applied in the production process. In this study will take data on the production process of lipstick filling in which the filling process of production has hours of work and uncertain results due to the absence of standard time and the exact amount of labor. This study tries to measure the workload of a lipstick fill operator with a work sampling method. From the measurements obtained different standard times; operator 1 = 0.469 minutes, operator 2 = 0.475 minutes, operator 3 = 0.483 minutes, operator 4 = 0.465 minutes, operator 5 = 0.466 minutes, operator 6 = 0.501 minutes and operator 7 = 0.5 minutes. Different standard time because the job description, rating factor and allowance each operator different. From the standard time that has been obtained, it can be seen the number of operators who should be employed to complete the process from the beginning to finish lipstick filling is 7 operators. The average percentage or workload of employees obtained based on the results of data analysis is 104.52% that the workload obtained by the operator is sufficient in accordance with workload that can be received by a worker.